2014
DOI: 10.1016/j.tsf.2013.11.123
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effects on the photoluminescence of terbium doped zinc oxide films

Abstract: effects on the photoluminescence of terbium doped zinc oxide films. Thin Solid Films, Elsevier, 2014Elsevier, , 553, pp.52-57. 10.1016Elsevier, /j.tsf.2013 Annealing effects on the photoluminescence of terbium doped zinc oxide films Terbium doped zinc oxide (Tb:ZnO) films were deposited by radio frequency magnetron sputtering on (100) single-crystalline silicon substrates at low temperature (T S = 100°C). In this work, structural changes, optical properties and the associated photoluminescence (PL) response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
(38 reference statements)
2
17
0
Order By: Relevance
“…43,70,71 The doping density obtained in the analyzed samples is around 3% as measured by energy-dispersive X-ray spectrometry. 43 (We remark that the high concentration of dopant would also make it possible to consider the material as an alloy between zinc oxide and terbium oxide. However, different stoichiometric ratios are possible for Tb x O y , and it is common practice to define the studied material as Tb-doped ZnO, briefly denoted as ZnO:Tb.)…”
Section: Measurement Of the Composition Of Binarymentioning
confidence: 91%
“…43,70,71 The doping density obtained in the analyzed samples is around 3% as measured by energy-dispersive X-ray spectrometry. 43 (We remark that the high concentration of dopant would also make it possible to consider the material as an alloy between zinc oxide and terbium oxide. However, different stoichiometric ratios are possible for Tb x O y , and it is common practice to define the studied material as Tb-doped ZnO, briefly denoted as ZnO:Tb.)…”
Section: Measurement Of the Composition Of Binarymentioning
confidence: 91%
“…The emission spectrum was obtained using the excitation wavelength of 488.0 nm of the 5 D 4 ← 7 F 5 transition (Figure 10a). Here, five emission bands are observed at 544.0, 584.7, 622.1, 649.9, and 684.2 nm, corresponding to the transition from the excited level 5 D 4 to 7 F 5 , 7 F 4 , 7 F 3 , 7 F 2 , and 7 F 1 , respectively [68,69].…”
Section: Photoluminescence Spectroscopymentioning
confidence: 91%
“…Since a F R ( ) is proportional to α and ZnO has direct allowed transitions, n is taken as 1/2. Thus, equation (11) can be transformed to: These changes in the values of E g depend on several factors such as grain size, carrier concentration, lattice strain, the size effect of the dopant metals in ZnO lattice [45]. Koao et al [46] showed that the grain size and the luminescence intensity increased when an increase in the amount of Mn 3+ ions occurred.…”
Section: Band Gap Calculationmentioning
confidence: 99%